2012
DOI: 10.1242/jeb.068064
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory coding in five moth species from two families

Abstract: SUMMARYThe aim of the present study was to determine what impact phylogeny and life history might have on the coding of odours in the brain. Using three species of hawk moths (Sphingidae) and two species of owlet moths (Noctuidae), we visualized neural activity patterns in the antennal lobe, the first olfactory neuropil in insects, evoked by a set of ecologically relevant plant volatiles. Our results suggest that even between the two phylogenetically distant moth families, basic olfactory coding features are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Thus, activation patterns for every isomeric pair of hexenal, hexenol and hexenyl acetate were used to calculate correlation coefficients providing a relative measurement of similarity (Bisch-Knaden et al, 2012). Repeated stimulations with the same structural isomer and the correlation coefficients thereof were used as control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, activation patterns for every isomeric pair of hexenal, hexenol and hexenyl acetate were used to calculate correlation coefficients providing a relative measurement of similarity (Bisch-Knaden et al, 2012). Repeated stimulations with the same structural isomer and the correlation coefficients thereof were used as control.…”
Section: Methodsmentioning
confidence: 99%
“…OSNs expressing the same receptor, and thus responding to the same set of odorants, converge onto the same glomerulus in the AL (Gao et al, 2000; Vosshall, 2000) as has been demonstrated for Drosophila melanogaster and indirectly also in several moth species (Hansson, 1997). Spatio-temporal patterns of neuronal activity representing sensory input to the AL can be visualized by optical imaging methods (Hansson et al, 2003; Skiri et al, 2004; Carlsson et al, 2005; Silbering and Galizia, 2007) enabling identification of compound- and blend-specific responses in the AL of M. sexta (Hansson et al, 2003; Bisch-Knaden et al, 2012; Kuebler et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly this odorant is the only fruit odorant in our stimulus set and might not be of ecological relevance for a male moth, while the other compounds are emitted by flowers or leafs. In vivo calcium imaging using bath-applied Calcium Green™ allowed us to monitor spatio-temporal changes in intracellular calcium levels in the AL, mainly reflecting the presynaptic calcium influx into OSNs (Galizia et al, 2000; Bisch-Knaden et al, 2012). In line with this observation, previous single sensillum recordings from the antenna of H. virescens (Hillier and Vickers, 2011) revealed that stimulation with mixtures of the pheromone component and linalool or Z3-hexenol strongly reduced the spiking activity of Z11-16:Ald-specific Ph-OSNs.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging data were processed as previously described (Bisch-Knaden et al, 2012) using custom-written software in IDL (ITT Visual Information Solutions). To quantify odor-evoked calcium signals, we identified the cumulus because of its clear response to Z11-16:Ald and its proximity to the antennal nerve entrance.…”
Section: Methodsmentioning
confidence: 99%
“…Wild and domesticated silkmoth females and females from three hawkmoth species (Manduca sexta, Acherontia atropos and Smerinthus ocellata) were dissected as described [19]. A fluorescent calcium indicator (Calcium Green-2 AM, Invitrogen) was dissolved in physiological saline solution [15] with 6% Pluronic F-127 (Invitrogen) to a concentration of 30 mmol.…”
Section: (H) Calcium Imaging (I) Mothsmentioning
confidence: 99%